Sold on love - Fuller, Kathleen (Fuller, Kathleen. Maple Falls romance, 2022)
"The townspeople of Maple Falls never dreamed the stylish real estate agent would have anything in common with everyone's favorite mechanic. But when these two get together, the spark plugs aren't the only thing creating a charge"--